A court of frost and starlight - Maas, Sarah J (New York : Bloomsbury, 2018)
"As Feyre navigates her first Winter Solstice as High Lady, she finds that those dearest to her have more wounds than she anticipated--scars that will have far-reaching impact on the future of their Court"--
"Bridges the events in A Court of Wings and Ruin and the upcoming novels in the series"--Publisher data sheet.
Keywords: Imaginary wars and battles -- Juvenile fiction; Courts and courtiers -- Juvenile fiction; Fairies -- Juvenile fiction; Winter solstice -- Juvenile fiction; Fantasy fiction